Unveiling the molecular environment of the ring nebula RCW78 - Cappa, Cristina Elisabet (2009)
Aims. We present a study of the ionized, neutral atomic, and molecular gas associated with the ring nebula RCW78 around the WR star HD117688 (=WR55) with the aim of analyzing the distribution of the associated gas and investigating its energetics. Methods. We base our study on 12CO(1-0) and 12CO(2-1) observations of the brightest section of the nebula carried out with the SEST telescope with angular resolutions of 45'' and 22'', respectively; and on complementary 12CO(1-0) data of a larger area obtained with the NANTEN telescope with an angular resolution of 2. ′ 7, Hi 21-cm line data taken from the ATCA survey, IRAS HIRES data, and radio continuum data at 4.85 GHz from the Parkes survey. Results. We report the detection of molecular gas having velocities in the range -56 to -33 kms -1 associated with the western region of RCW78. A few patches of molecular gas possibly linked to the eastern faint section are detected. The CO emission appears concentrated in a region of 23′ ×18′ in size, with a total molecular mass of (1.3 ±0.5) ×105 M ⊙, mainly connected to the western section. The analysis of the neutral atomic gas distribution reveals the Hi envelope of the molecular cloud, while the radio continuum emission shows a ring-like structure, which is the radio counterpart of the optical nebula. The gas distribution is compatible with the western section of RCW78 having originated in the photodissociation and ionization of the molecular gas by the UV photons of the WN7 star HD117688, and with the action of the stellar winds of the WR star on the surrounding gas. In this scenario, the interstellar bubble expanded more easily towards the east than towards the west due to the lack of dense molecular gas in the eastern section. The proposed scenario also explains the off center location of WR55. A number of infrared point sources classified as YSO candidates showed that star formation activity is present in the molecular gas linked to the nebula. The possibility that the expansion of the bubble triggered star formation in this region cannot be discarded.